Economic returns of oat (Avena sativa) under various cutting intervals - HUSSAIN, ASHIQ; KHAN, SARTAJ; MOHAMMAD, DOST; BHATT, M B (The Indian Journal of Agricultural Sciences, 2013)
An experiment was conducted during 1987-89 to assess 5 varieties of oat (Avena sativa L.) for fodder yield. seed yield and gross income under different harvesting intervals. 'PO 2 LV 65','S 81' and 'Swan' gave the maximum green-fodder yield (58.90,54.99 and 54.58 tonnes/ha) and gross income (Rs 14 750, 13 800 and 13 720/ha) when harvested only for fodder at 50%, flowering stage. The highest seed yield (2.19tonnes/ha) and gross income (Rs 12 380/ha) were obtained from 'PD 2 LV 65' harvested only for seed. 'Swan' cut for fodder after 70 and 85 days of planting and then left for seed gave respectively 2.04 and 2.07 tonnes/ha seed yield and Rs 11 520 and 11 590/ha gross income. The maximum cash income from fodder + seed was received from 'Swan' harvested for fodder after 85 and 100 days (Rs 18 600 and 18 980/ha) and 'PD 2 LV 65' harvested 115 days after planting (Rs 18 380/ha). Thus it was more economical to cutoat for fodder 85-115 days after planting and then for seed at maturity,